Experimental investigation of the parameters of additively manufactured coaxial swirl injectors - Samir Vekilov; Volodymyr Lipovskyi; Roman Marchan; Artem Lohvynenko (Challenges and Issues of Modern Science)
Modern development of the intense competition on the market of Liquid Propellant Rocket Engines (LPRE) is mostly driven by occurrence of many private space companies, crowdfunding space projects, etc., which inevitably leads engineers to seeking of rational solutions with the aim of decreasing production costs along with increasing of the efficiency of the parts. Usually for successful development of the rocket engine costly equipment as well as advanced manufacturing experience is in need which explains high overall manufacturing cost.